2015
DOI: 10.4236/pp.2015.67032
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of siRNA Delivery Method into the Liver by Sequential Injection of Polyglutamic Acid and Cationic Lipoplex

Abstract: Previously, we developed a novel siRNA transfer method to the liver by sequential intravenous injection of poly-L-glutamic acid (PGA) and cationic liposome/siRNA complex (cationic lipoplex). In this study, we examined the effects of the charge ratio (+/−) of cationic liposome/siRNA, molecular weight of PGA and cationic lipid of cationic liposome on the biodistribution of siRNA after sequential injection of PGA plus cationic lipoplex. When 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP)/cholesterol (Chol) lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Moreover, intramuscular, intraperitoneal, or subcutaneous injection of CS into mice before intravenous injection of DOTAP/Chol lipoplexes also resulted in siRNA accumulation mainly in the liver [88]. We found that regardless of the injection route of CS, the concentration of CS in serum needed to [86][87][88]. In sequential injection, at 1 min after intravenous injection of 1 mg CS or αPGA, DOTAP/Chol lipoplexes with Cy5.5-labeled siRNA (Cy5.5-siRNA) were administered intravenously to mice [86][87][88].…”
Section: Sequential Injection Of Anionic Polymer and Sirna Lipoplexesmentioning
confidence: 83%
See 3 more Smart Citations
“…Moreover, intramuscular, intraperitoneal, or subcutaneous injection of CS into mice before intravenous injection of DOTAP/Chol lipoplexes also resulted in siRNA accumulation mainly in the liver [88]. We found that regardless of the injection route of CS, the concentration of CS in serum needed to [86][87][88]. In sequential injection, at 1 min after intravenous injection of 1 mg CS or αPGA, DOTAP/Chol lipoplexes with Cy5.5-labeled siRNA (Cy5.5-siRNA) were administered intravenously to mice [86][87][88].…”
Section: Sequential Injection Of Anionic Polymer and Sirna Lipoplexesmentioning
confidence: 83%
“…We found that regardless of the injection route of CS, the concentration of CS in serum needed to [86][87][88]. In sequential injection, at 1 min after intravenous injection of 1 mg CS or αPGA, DOTAP/Chol lipoplexes with Cy5.5-labeled siRNA (Cy5.5-siRNA) were administered intravenously to mice [86][87][88]. Ex vivo images of dissected tissues (A) and tissue sections (lung and liver) (B) were obtained at 1 h after injection of siRNA lipoplexes.…”
Section: Sequential Injection Of Anionic Polymer and Sirna Lipoplexesmentioning
confidence: 92%
See 2 more Smart Citations
“…Previously, we developed a ternary complex of siRNA, cationic liposomes, and anionic polymer, and we found that chondroitin sulfate C (CS-C) or PGA coating of the cationic lipoplex produced safe systemic vectors [10]. Recently, we reported that intravenous injection of cationic lipoplex 1 min after intravenous injection of CS-C or PGA into mice could deliver siRNA to the liver efficiently without accumulation in the lungs [11,12]. However, it was not clear whether siRNA delivery into the liver by sequential injection of anionic polymer plus cationic lipoplex was affected by the injection route of the anionic polymer.…”
Section: Introductionmentioning
confidence: 97%